The unfolded protein response affects readthrough of premature termination codons. Issue 5 (4th April 2014) - Oren, Yifat S; McClure, Michelle L; Rowe, Steven M; Sorscher, Eric J; Bester, Assaf C; Manor, Miriam; Kerem, Eitan; Rivlin, Joseph; Zahdeh, Fouad; Mann, Matthias; Geiger, Tamar; Kerem, Batsheva
Synopsis <boxed-text content-type="graphic" id="emmm201303347-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text> Activation of the unfolded protein response (UPR) governs the response to readthrough treatment by regulating the levels of transcripts with PTCs. Furthermore, a novel nonsense‐mediated mRNA decay (NMD)‐UPR feedback loop is described. Proteome analyses show substantial differences in unfolded protein response (UPR) activation between patients carrying PTCs, correlated with their response to readthrough treatment. UPR activation enables CFTR and XLF function following readthrough treatment. Proteome analyses uncover inverse correlation between UPR and nonsense‐mediated mRNA decay (NMD), suggesting a feedback‐loop mechanism between these homeostatic pathways. The NMD‐UPR feedback loop augments both UPR activation and NMD attenuation. The NMD‐UPR feedback loop enhances the response to readthrough treatment, highlighting its clinical importance.